2015
DOI: 10.2459/jcm.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of circulating microRNAs in heart failure

Abstract: We demonstrated the increased expression levels of circulating miRNAs in CHF as compared with controls. Moreover, miR-182 was found to be a potential prognostic marker in CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 26 publications
0
44
0
2
Order By: Relevance
“…In male fetuses, 56 miRNAs were differentially expressed with IUGR (p<0.05, Figure 4), 12 of them were upregulated and 44 downregulated. Overall, 26 miRNAs were mapped to human; fourteen of them ( hsa-miR-1, -26a, -27b, -28, - 30e, -98, -99b, -143, -148a, -181a, -208b, -299-3p, -378, and -483 ) were previously linked to CVD [53, 61-72]. Only three of differentially expressed miRNAs - hsa-miR-1, -378, and -143 - were common for male and female IUGR fetuses and showed a significant reduction with IUGR vs. control.…”
Section: Resultsmentioning
confidence: 99%
“…In male fetuses, 56 miRNAs were differentially expressed with IUGR (p<0.05, Figure 4), 12 of them were upregulated and 44 downregulated. Overall, 26 miRNAs were mapped to human; fourteen of them ( hsa-miR-1, -26a, -27b, -28, - 30e, -98, -99b, -143, -148a, -181a, -208b, -299-3p, -378, and -483 ) were previously linked to CVD [53, 61-72]. Only three of differentially expressed miRNAs - hsa-miR-1, -378, and -143 - were common for male and female IUGR fetuses and showed a significant reduction with IUGR vs. control.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple clinical studies have been conducted to carefully characterize the miRNA profile in healthy versus advanced HF patients [146,147]. These clinical studies showed that miRNA profiles differ not only between HF and non-HF groups, but also between HF patients of differing ages and etiologies [129,148,149].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Two miRNAs, miR-624 and miR-339, were deregulated in ischemic heart disease and coronary artery disease [53, 54]. MiR-744 was deregulated in patients with chronic congestive heart failure [55]. Several miRNAs were detected in cardiac tissue at different stages of development and are highly expressed in the fetal heart, including miR-212, miR-210 and miR-423 [41].…”
Section: Discussionmentioning
confidence: 99%